PELATIHAN RELAWAN TANGGAP DARURAT DAN PERUBAHAN PERILAKU DI ERA PANDEMI COVID-19 BAGI PARA GURU ANGGOTA PGRI DI KOTA JAMBI DAN KABUPATEN MUARO JAMBI - Humaryanto Humaryanto; Mifftahurahmah Mifftahurahmah; Huntari Harahap; Putri Sari Wulandari (Universitas Jambi, 2022)
ABSTRACT Corona Virus Disease 2019 has infected about 126,063 people in the world, and caused 4,616 deaths. Therefore, since March 12, 2020, COVID-19 has been designated by WHO as a pandemic in the world. In Indonesia alone, COVID-19 has caused 1,528 people who were positive for Covid-19 and 136 people died. One of the efforts made is by making Government regulation no. 2 of 2020 concerning Large-Scale Social Restrictions, as well as establishing a public health emergency due to the Covid-19 virus through Presidential Decree, no. 11 of 2020. The purpose of this community service activity is to train teachers as volunteers. in emergency response situations and prevention efforts by changing behavior in the Covid-19 pandemic era. The method used is counseling and training through virtual webinar activities with the topics of BHD and Emergency knowledge education in schools, ISOMAN patient education at home, Prevention of (tropical) infectious diseases and vaccinations, Post-Covid-19 psychological problems. This activity was attended by 104 teachers from Jambi City (79 people; 75.96%) and Muaro Jambi Regency (25 people; 24.04%). Participants consisted of kindergarten teachers (1 person, 0.96%), elementary school teachers (66 people, 63.64%), and junior high school teachers (34 people, 33.68%), and high school teachers (3 people, 2.88 %). This community service concludes, counseling and training can increase teacher knowledge in emergency response situations and prevention efforts by changing behavior in the Covid-19 pandemic era. Keywords: Training, Volunteers, Emergency Response, Covid-19 ABSTRAK Corona Virus Disease 2019 telah menjangkiti sekitar 126.063 orang di dunia, dan menyebabkan 4.616 kematian. Oleh karena itu, sejak tanggal 12 Maret 2020, covid-19 ditetapkan oleh WHO sebagai pandemic di dunia. Di Indonesia sendiri, covid-19 sudah menyebabkan 1.528 orang yang positif terkena Covid-19 dan 136 orang meninggal. Salah satu usaha yang dilakukan yakni dengan membuat peraturan Pemerintah no 2 Tahun 2020 tentang Pembatasan Sosial Berskala Besar, serta penetapan darurat kesehatan masyarakat akibat virus Covid-19 melalui Kepres, no.11 tahun 2020. Tujuan dari kegiatan pengabdian masyarakat ini adalah melatih guru sebagai relawan dalam situasi tanggap darurat dan upaya pencegahan dengan perubahan perilaku di era pandemi Covid-19. Metode yang digunakan adalah penyuluhan dan pelatihan melalui kegiatan webinar virtual dengan topik Edukasi pengetahuan BHD dan Kegawatdaruratan di sekolah, Edukasi pasien ISOMAN di rumah, Pencegahan penyakit Infeksi (tropis) dan vaksinasi, Permasalahan Psikologi post Covid-19. Kegiatan ini dihadiri oleh 104 orang guru yang berasal dari Kota Jambi (79 orang; 75,96%) dan Kabupaten Muaro Jambi (25 orang; 24,04%). Peserta terdiri dari guru TK (1 orang, 0,96%), guru SD (66 orang, 63,64%), dan guru SMP (34 orang,33,68%), serta guru SMA (3 orang, 2,88%). Pengabdian masyarakat ini memperoleh simpulan, penyuluhan dan pelatihan dapat meningkatkan pengetahuan guru dalam dalam situasi tanggap darurat dan upaya pencegahan dengan perubahan perilaku di era pandemi Covid-19. Kata Kunci : Pelatihan, Relawan, Tanggap darurat, Covid-19